Pré-eclâmpsia: inter-relação dos sistemas hemostático e inflamatório - Melina de Barros Pinheiro (2012)
Preeclampsia (PE) is a multifactorial disease characterized by hypertension and proteinuria after 20 weeks of gestation. The PE etiology is not known yet, and the disease occurs only in the presence of the placenta. Clinically it is important to diagnose the severe form of the disease, in which blood pressure and proteinuria are even higher. PE is associated with vascular dysfunction, as well as to exacerbation of coagulation, which is higher than those observed in normotensive pregnant women. The involvement of the immune system in the PE pathogenesis is well accepted and this disease is associated with a high inflammatory condition. Several polymorphisms in the genes of pro-inflammatory cytokines appear to be associated with PE occurrence. It is known that components of the hemostatic system are able to activate the inflammatory system and vice versa. Thus, the aim of this study was to investigate the relationship between hemostatic and inflammatory systems in severe PE, by determining plasma levels of hemostatic markers and cytokines, as well as evaluating the relationship of polymorphisms in cytokine genes and the PE occurrence. A total of 331 women were evaluated (108 non-pregnant women, 107 normotensive pregnant women, and 116 pregnant women with severe PE). Severe PE was defined as blood pressure 160/110mmHg and proteinuria > 2 g L-1. PAI-1 and D-Di Plasma levels were measured by ELISA (Kit IMUBIND® PLASMA PAI-1 and IMUCLONE® Kit D-Dimer American Diagnostica® Inc., Stamford, USA, respectively). The cytokines IL-8, IL-6, IL-1â, TNF-á, IL-12, IFN-ã, IL-4, IL-5 and IL-10 were determined by flow cytometry (Cytometric Beads Array - CBA; BD Biosciences Pharmingen, USA). The determination of polymorphisms in the IL-6, IL-10, IFN-ã and TNF-á genes was performed by PCR-SSP (Cytokine Genotyping Tray; One Lambda, Inc. Canoga Park, CA). The data obtained in this study indicate that plasma markers of coagulation/fibrinolysis and inflammatory cytokines IL-6, IL-8 and IFN-ã are elevated in severe PE and there is not a strong correlation between them. Furthermore, severe PE is associated with high frequency of T/T genotype in IFN-ã gene (+874) and this genotype determines the increase of this cytokine, while the other polymorphisms do not exert any role in this disease. The systematic review and meta-analysis investigating the D-Di levels in PE revealed that this marker is a promising candidate for monitoring of PE.